State of the science for ground truthing in crop analytics for smallholder farmers - Olofsson, P.; Koo, Jawoo; Ghosh, A.; Krishnamurthy, P. K. (2021)
The number of people experiencing food insecurity has increased for the third consecutive year, a worrying reversal of progress since the 1990s (FAO, 2020). Addressing food insecurity and achieving the United Nations' second sustainable development goal to eradicate hunger by 2030 will require more timely and accurate information on agricultural yield, food availability, and land use, with data that are relevant for the most vulnerable populations. Special attention should focus on smallholder farming, which continues to dominate the agricultural landscape of sub-Saharan Africa, Asia, Latin America, and the Middle East. While the definitions of a "smallholder farm" differ, as of 2018, 475 million out of 580 million farms worldwide were smaller than two hectares in size and that more than 500 million were family-operated (Lowder et al., 2018). These farms are often intercropped, used primarily for home consumption, and operated by a single household or family.